Artificial Intelligence in ELT: A Writing-centered Approach to Language Development (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The current paper investigates the transformative role of artificial intelligence (AI) in English Language Teaching (ELT), specifically in the enhancement of learners’ writing skills. Since the COVID-19 pandemic there has been a large shift towards remote learning, which has accelerated the integration of AI-driven tools into educational contexts. In this study, we aim to explore how intelligent tools such as chatbots, and generative AI models assist learners in reducing language anxiety, boosting grammar and vocabulary, and building confidence. Drawing on recent empirical studies and practical examples, we highlight the pedagogical benefits of adopting AI tools in ELT, and emphasize its capacity to encourage autonomy, increase learners’ motivation, and improve their performance.